Climate Change Reveals Contractions and Expansions in the Distribution of Suitable Habitats for the Neglected Crop Wild Relatives of the Genus Vigna (Savi) in Benin - Manda, Leonard; Idohou, Rodrigue; Assogbadjo, Achille Ephrem; Agbangla, Clement (Frontiers in Conservation Science, 2022)
The urgency of conserving crop wild relatives for securing global food security amid climate change threats to biodiversity is widely recognized. Yet, fundamental knowledge gaps in the distribution of crop wild relatives, partly due to less conservation attention as these species are not morphologically charismatic, are limiting their effective conservation. To contribute to addressing these conservation biases, and optimise crop wild relative conservation, this study assessed the present-day distribution of 15 Vigna crop wild relatives in Benin and forecast the potential impact of climate changes on the species distribution under two future climate scenarios (RCP 4.5 and RCP 8.5) at the 2055-time horizon. Records (1432) of the species were gathered in addition to 12 climate-related and eight soil-related variables implemented in MaxEnt, SDM Tools, and GIS technology. The AUC (range: 0.914 - 0.997; median= 0.956; mean= 0.957) and TSS (range: 0.617 - 0.876; median= 0.771; mean= 0.774) values indicated that the models were of acceptable accuracy. Precipitation of the driest quarter and isothermality were found to influence the distributions of most models. The influence of soil texture was more apparent on the small-sized distributed models like V. laurentii and V. oblongifolia. Substantial shifts in the potentially suitable habitats were observed under future climate scenarios, depicting a northerly expansion in one-third of the species. Nearly half of the species were suggested to lose between 5 % and 40 % of their potentially suitable habitats due to climate change by 2055, the greatest losers being V. multinervis and V. unguiculata subsp. baoulensis. The existing protected area network in Benin may be less effective to conserve Vigna crop wild relatives as it covers only about 10 % of the total potentially suitable habitat for the studied species under both current and future climate conditions. This appears to be the first evaluation record of the impacts of climate change on multiple wild Vigna species at a local scale. These findings provide a crucial step towards the development of sustainable strategies for in situ conservation and further explorations for ex situ conservation of crop wild relatives in Benin while underscoring the urgency of such actions.